What corpora tell us about the grammaticalisation of voice in get-constructions - Hundt, Marianne (Studies in language, 2001)
Grammaticalisation studies are a potential meeting ground for theoretical linguistics and corpus-based approaches. The present paper uses evidence from the ARCHER corpus to investigate the relationship between frequency and the grammaticalisation of the get-passive. It seeks to verify whether the grammaticalisation of the passive function is reflected in an increase in the overall frequency of get, and whether grammaticalised patterns of get have spread at the expense of its lexical use. Givón/Yang (1993) have singled out several patterns that were involved in the grammaticalisation of the get-passive. Data from ARCHER are analysed to find out which of these patterns were frequent and which were of marginal importance. Finally, evidence from standard one-million-word corpora is used to test existing hypotheses on the maturation of the get-‘passive’. These data show that it has not lost its middle semantics and come closer to a true passive.